2010
DOI: 10.1681/asn.2009101017
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Variability Does Not Predict Mortality in European Hemodialysis Patients

Abstract: Patients with CKD exhibit significant within-patient hemoglobin (Hb) level variability, especially with the use of erythropoiesis stimulating agents (ESAs) and iron. Analyses of dialysis cohorts in the United States produced conflicting results regarding the association of Hb variability with patient outcomes. Here, we determined Hb variability in 5037 European hemodialysis (HD) patients treated over 2 years to identify predictors of high variability and to evaluate its association with all-cause and cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 23 publications
6
48
1
1
Order By: Relevance
“…Each 3-mo increment in the duration of ESA therapy decreased the risk of haemoglobin variability by 6%. In a study involving 5,037 ESKD patients on haemodialysis, the risk of developing haemoglobin variability was more than twice in patients on ESAs, compared to those not on ESAs (Eckardt et al, 2010). These findings suggest that the need of ESA rather than ESA therapy per se leads to haemoglobin variability (See Table 1).…”
Section: Esa Therapymentioning
confidence: 98%
See 3 more Smart Citations
“…Each 3-mo increment in the duration of ESA therapy decreased the risk of haemoglobin variability by 6%. In a study involving 5,037 ESKD patients on haemodialysis, the risk of developing haemoglobin variability was more than twice in patients on ESAs, compared to those not on ESAs (Eckardt et al, 2010). These findings suggest that the need of ESA rather than ESA therapy per se leads to haemoglobin variability (See Table 1).…”
Section: Esa Therapymentioning
confidence: 98%
“…al., 2009;). On the other hand, 82 to 90% of ESKD patients on dialysis exhibit haemoglobin variability (Ebben et al, 2006;Eckardt et. al., 2010;Gilbertson et.…”
Section: Prevalencementioning
confidence: 99%
See 2 more Smart Citations
“…When the Hb level exceeds the target, the ESA dose should be reduced without discontinuing treatment in order to avoid an excessive decrease in the Hb level that can only be corrected with higher ESA doses, because this may lead to Hb cycling. This cause-effect relationship is far from proven, but it has been related to greater mortality at the patient [35] and facility [36] level, although a recent observational study of 5,037 European HD patients found that the risk for mortality was only higher in patients with persistently low Hb levels (Ͻ11 g/dL) or levels that fluctuated between the target range and Ͻ11 g/dL [37].…”
Section: Clinical Use Of Esasmentioning
confidence: 99%